European Congress of Mathematics 2018
DOI: 10.4171/176-1/2
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polyhedra and their volumes

Abstract: We discuss some recent results on flexible polyhedra and the bellows conjecture, which claims that the volume of any flexible polyhedron is constant during the flexion. Also, we survey main methods and several open problems in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Another proof, which is also limited to the case d = 3, was published in 1997 in [8] (see also an expository paper [30]). For d 4, the Bellows Conjecture was proved by A.A. Gaifullin in 2014 in [12] and [13] (see also an expository paper [17]).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another proof, which is also limited to the case d = 3, was published in 1997 in [8] (see also an expository paper [30]). For d 4, the Bellows Conjecture was proved by A.A. Gaifullin in 2014 in [12] and [13] (see also an expository paper [17]).…”
Section: Introductionmentioning
confidence: 95%
“…Now we already know that any flexible polyhedron in Euclidean 3-space preserves the total mean curvature (see [1]), enclosed volume (there are especially many articles devoted to this issue, so we point out several of them in chronological order: [23], [24], [25], [10], [26], [27], [14], and [13]), and Dehn invariants (see [16]). The reader can find more details about the theory of flexible polyhedra in the above mentioned articles, as well as in the following review articles, which we list in chronological order: [21], [8], [29], [28], and [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gluck [13] then showed that “almost all” simply connected polyhedra are rigid as well. The research then focused on finding necessary and sufficient conditions for the flexibility of polyhedra, and it is still an active research field, as witnessed by, among others, recent works by Gaifullin [8] and Alexandrov [2, 3]. In the latter, Alexandrov proved that the edge lengths of a flexible (orientable) polyhedron with triangular faces must satisfy a Q$\mathbb {Q}$‐linear relation.…”
Section: Introductionmentioning
confidence: 99%
“…Gluck [Glu75] then showed that "almost all" simply connected polyhedra are rigid as well. The research then focused on finding necessary and sufficient conditions for the flexibility of polyhedra, and it is still an active research field, as witnessed by, among others, recent works by Gaifullin [Gai18] and Alexandrov [Ale19,Ale20].…”
Section: Introductionmentioning
confidence: 99%